Stochastic models in reliability, network security and system safety : essays dedicated to Professor Jinhua Cao on the occasion of his 80th birthday /: essays dedicated to Professor Jinhua Cao on the occasion of his 80th birthday. ([2019]) - Unknown
No abstract available